Supported Liquid Membranes Based on Bifunctional Ionic Liquids for Selective Recovery of Gallium - Haitao Zhou; Yuxi Ye; Yuefei Tan; Kailun Zhu; Xinmin Liu; Hongjing Tian; Qingjie Guo; Lingyun Wang; Shuju Zhao; Yang Liu (Membranes, 2022)
In this work, separation and recovery of gallium from aqueous solutions was examined using acid-base bifunctional ionic liquids (Bif-ILs) in both solvent extraction and supported liquid membrane (SLM) processes. The influence of a variety of parameters, such as feed acidity, extractant concentration and metal concentration on the solvent extraction behavior were evaluated. The slope method combined with FTIR spectroscopy was utilized to determine possible extraction mechanisms. The SLM containing Bif-ILs demonstrated highly selective facilitated transport of 96.2% Ga(III) from feed to stripping solution after optimization. During the evaluation of the separation performance of SLM for the transport of Ga(III), in the presence of Al(III), Mg(II), Cu(II) and Fe(II), 88.5% Ga(III) could be transported with only 6% Fe(II) and a nil quantity of other metals co-transported. SLM exhibited excellent long-time stability in five repeated transport cycles. Highly selective transport and separation performance was achieved using the SLM containing Bif-ILs, indicating considerable potential for application in Ga(III) recovery.